Research Trends and Knowledge Networks of SME in the Visegrád Group (V4) Countries: a Bibliometric Exploration - Talukder, Saurav Chandra (Acta Carolus Robertus, 2024)
The paper provides a bibliometric study of the V4 countries' small and medium-sized enterprise (SME) research patterns and knowledge networks. Using data (n=352) from the Web of Science database between 2001 and 2022, researcher examines Key features of SME research, such as publishing trends, influential sources and institutions, well-known authors, and conceptual structure of the literature. The research shows that there has been an uptick in scholarly articles focusing on small and medium-sized enterprises (SMEs) in recent years, especially in 2019. The top three journals by number of articles published are the Journal of Competitiveness, Oeconomia Copernicana, Transformations in Business & Economics. The three most notable authors in this field of research are Belas Jaroslav, Kljucnikov Aleksandr, and Cepel Martin. On the other hand, the most influential institutions are Tomas Bata University Zlin, followed by University of Zilina  and Alexander Dubcek University of Trencin in Slovakia. Furthermore, researcher employs keyword maps, thematic maps, and conceptual structure maps to uncover recurrent themes like Industry 4.0, digital transformation, SME finance, performance, and internationalization of SMEs. This study has important implications for policymakers, researchers, and practitioners who are interested in fostering the growth and innovation of small and medium-sized enterprises (SMEs) in the V4 countries.
Keywords: SMEs,; Industry 4.0; Digital transformation; V4 countries; Bibliometric Analysis